The films of Mary Harron. - Barrett, Kyle. (Edinburgh : Edinburgh University Press, 2021)
Offers the first first book-length study of Mary Harron's career and works.
Frontmatter -- Contents -- List of Figures -- Acknowledgments -- Notes on Contributors -- Introduction -- Part I Biopics -- 1 I Shot Andy Warhol: Fame, Notoriety, and Mary Harron's Anti-biopics -- 2 On the Other Side of the Icon: Making Images and Restaging Celebrity Spectacle in Anna Nicole -- Part II Feature Films and Production Contexts -- 3 Dream of the '90s: Mary Harron in Indiewood -- 4 "I Like to Dissect Girls": Mary Harron's American Psycho as Gendered Metafiction -- 5 "And Then I Met Lucy": Perfection, Same-sex Desire, and Social Control in Mary Harron's The Moth Diaries -- 6 Charismatic Breadwinner Killer: Gender Power Relations in Charlie Says -- Part III Television and Short Film Production -- 7 Death to Disposal: Echoes of American Psycho in "The Rainbow of Her Reasons" (Six Feet Under) -- 8 Sartorial Interventions: When Fashion and Film Collide -- Filmography -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Harron, Mary -- Criticism and interpretation; Harron, Mary; Motion picture producers and directors -- Canada; Women motion picture producers and directors -- Canada; Producteurs et réalisateurs de cinéma -- Canada; Productrices et réalisatrices de cinéma -- Canada; Motion picture producers and directors; Women motion picture producers and directors; Canada; Criticism, interpretation, etc